Simulation and Control of a Ball Screw System Actuated by a Stepper Motor with Feedback - Cloutier, John (University of Guelph, 2014)
This thesis presents an investigation on motion control of a ball screw system actuated by a permanent magnet stepper motor (PMSM). Using a PMSM for high speed application to operate in feedforward mode is difficult; therefore, a servo system needs to be developed to allow operations at those velocities. To convert a PMSM into a servo system, a linearizing program called a preprocessing filter (PPF) is used to convert the controller signal into a velocity signal the stepper driver can use. The filter was developed along with the methods for extraction of the PPF parameters. Vibrations information, obtained from the rotational velocities, was gathered in order to ensure optimal design and performance of the PPF. The system velocity causing the critical vibrations was excluded. Using the PPF, two types of controllers, Proportional (P) and Proportional Derivative (PD), were designed and implemented for precise displacement of the PSMS. It was found that the PD controller is superior to the P controller in terms of settling time to peak for the PMSM system. As well, the P controller for the FDS outperformed the PD controller in terms of settling time. Madawaska Maliseet First Nation